THE EFFECT OF SERVICE EXCELLENCE ON CUSTOMER SATISFACTION AT LOMBOK VAGANZA HOTEL & CONVENTION, MATARAM CITY, INDONESIA - Halus Mandala; Muhammad Ridla Ridla; Dyah Estu Larasati Dyah Estu Larasati (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study aims to examine the effect of service excellence on customer satisfaction at Lombok Vaganza Hotel & Convention, Mataram City, Indonesia. A quantitative approach employing a descriptive research design was adopted. The study population comprised all guests who stayed at Lombok Vaganza Hotel & Convention between July 2024 and June 2025, totaling 4,457 individuals. The sample size was determined using the Slovin formula, resulting in 98 respondents. A combination of stratified sampling and incidental sampling techniques was employed to select the respondents. Data were collected through questionnaires, observations, and documentation and subsequently analyzed using simple linear regression with IBM SPSS Statistics version 25. The findings indicate that service excellence has a positive and statistically significant effect on customer satisfaction. This is evidenced by a regression coefficient of 0.287 with a significance level of 0.000 (p < 0.05), indicating that improvements in service excellence are associated with higher levels of customer satisfaction. Furthermore, the coefficient of determination (R²) of 0.136 indicates that service excellence explains 13.6% of the variance in customer satisfaction, while the remaining 86.4% is attributable to other factors beyond the scope of the research model. These findings suggest that service excellence is an important determinant of customer satisfaction, although additional factors also contribute to customers' overall evaluations. Practically, the results imply that hotel management should continuously improve service quality while simultaneously enhancing other aspects of the guest experience to achieve higher levels of customer satisfaction and strengthen the hotel's competitiveness.